The Effectiveness of Positive Therapy on Fear of Intimacy and Suicidal Thoughts in Girls Experiencing Romantic Relationship Dissolution - Dehghan, Sepideh; Shabani Minaroodi, Roghayegh; Eslami, Sajjad (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to determine the effectiveness of positive therapy on fear of intimacy and suicidal thoughts in girls experiencing romantic relationship dissolution. Methods: This semi-experimental study employed a pretest-posttest-follow-up design with a control group. The statistical population included 401 individuals who visited a counseling center in Tehran. From this population, 30 girls experiencing romantic relationship dissolution were selected based on inclusion and exclusion criteria and were randomly assigned to experimental and control groups, each consisting of 15 individuals. Data were collected using the Suicidal Ideation Questionnaire and the Fear of Intimacy Scale. The experimental group received 8 sessions of positive therapy, while the control group received no intervention. Data were analyzed using repeated measures analysis of variance (ANOVA) with SPSS.24 software. Findings: The results showed that positive therapy had a significant effect on reducing fear of intimacy (F=24.87, P<0.001) and suicidal thoughts (F=19.87, P<0.001) in girls experiencing romantic relationship dissolution. Conclusion: It can be concluded that positive therapy leads to a reduction in fear of intimacy and suicidal thoughts in girls experiencing romantic relationship dissolution and can be effective in reducing psychological problems in this population.